Management Rights of Mining Goods in the Perspective of Islamic Economics (Case Study of PT Timah Indonesia) - Kafi, Abd; Khusnudin, Khusnudin (Jurnal Iqtisaduna, 2025)
This study aims to analyze PT's governance of tin mining. Timah in Indonesia with an Islamic economic perspective. This objective is based on the fact that Indonesia has a significant tin content, which PT then manages, and the discovery of major corruption cases in the sector. In addition, there are similarities in the objectives of the public goods view between the 1945 Constitution and the principles of Islamic economics. However, several studies have shown that there are still differences in the governance of public goods. The research method used is descriptive qualitative with case studies. From the results of this study, it is concluded that in Islamic economics, tin is a public good, which is the right of all people, whose management is handed over to the state. The governance of tin mining by PT Timah Tbk is governed by the governance of public goods in Islamic economics because PT Timah Tbk is a member of MINID under the auspices of BUMN, whose 65% shares are controlled by the state, so the state has control and supervision in mining governance.